Key policies and socio-economic growth factors of rural areas in the European Union - Mirela-Adriana Rusali (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Economic growth driven by a broad spectrum of factors is essential to long-term, sustainable development. From this perspective the paper approaches the economic growth of rural areas in Romania in light of the Europe 2020 Strategy, in order to identify specific indicators and national targets. The work falls within the management of rural development policy, in the current context of CAP's funding period 2014-2020. In line with the strategic objectives of improving the competitiveness of agriculture, the sustainable management of natural resources and balanced territorial development of rural areas, the results based on a comparative analysis of main socio-economic indicators related to the EU member states, stresses certain variables that present pressure or security risk upon Romania's rural economy.
Keywords: O1; F6; Q0; O5; 330; rural development; socio-economic indicators; growth; European Union